UPAYA LIMITATIF UNDANG – UNDANG CIPTA KERJA TERHADAP PARTISIPASI PUBLIK DALAM PENGELOLAAN LINGKUNGAN - Putri, Tania Octavia (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2024)
This research aims to identify and analyze the legal conception and legal character inthe Job Creation Law in environmental management, in addition to the aim of promoting ease of licensing and efforts to create an investment climate. Simplification of regulations in the long run will erode the government's attention to environmental management. First, the government in this case overrides one aspect of sustainable development, namely development that pays attention to environmental sustainability through efforts to simplify the stages of environmental permits, assessment team institutions, environmental feasibility tests. Second, efforts to narrow public participation by limiting suggestions and criticism from communities directly affected by environmental licensing do not reflect the character of responsive law that is present to answer problems in society.